The Empowering the Elderly: Psychoeducation as an Effort to Prevent Loneliness - Pangesti, Ary Tri Rahayu; Nurhamida, Yuni (Yayasan Adra Karima Hubbi, 2024)
The elderly population in Malang City is projected to reach 114,334 individuals, presenting various challenges related to health, cognitive function, and socio-emotional well-being. This study explores the role of psychoeducation in preventing loneliness among the elderly. According to Erik Erikson's theory, elderly individuals face the stage of